(untitled) (Green University Review of Social Sciences, 2022)
The incredibly patient Santiago, the protagonist of Ernest Hemingway’s The Old Man and the Sea and the stubborn and revengeful Captain Ahab in Herman Melville’s Moby Dick present an arresting similarity if their fate and fatal ending are observed. Both the protagonists are driven by their urge to triumph over their situations – Santiago from poverty and social shame, Ahab from obsession with vengeance. Both in the end lose the capacity for reasoning which leads them towards their doom. Their persona – the best fisherman of an area for Santiago and the best whale hunter in a community – gets hurt and drives them towards their demise. They both want to be the conquerors of the sea and finally are conquered by their desires. This research identifies both the characters in social image crisis. Drawing upon the works of Sigmund Freud and Carl Gustav Jung, the paper first analyses the personality levels and different drives in human beings. Then, how the drives motivate the two characters and their personas will be discussed. Overall, the paper criticizes the choices of the two characters in the light of psychoanalysis. Green University Review of Social Sciences Dec 2021; 7(1-2): 175-187